Chicken Toxoplasmosis in Different Types of Breeding: A Seroprevalence Survey in Southern Iran - Asgari, Q.; Mohajeri, F. Akrami; Kalantari, M.; Esmaeilzadeh, B.; Farzaneh, A.; Moazeni, M.; Ghalebi, S.R.; Saremi, F.; Kalyani, M. Zarifi; Motazedian, M.H. (International Journal of Poultry Science, 2008)
Since the meat of chicken is considered one of the sources of the human infection, this study was undertaken to compare the prevalence of toxoplasmosis in free-ranging with semi-industrial and industrial chickens (Gallus gallus domesticus) in Shiraz, Southern, Iran. 203 serum samples from free-ranging chickens of sub-urban districts, 50 serum samples of semi-industrial chickens which rearing in restricted location and 444 serum samples of industrial chickens from slaughters were collected and tested for toxoplasmosis by IFAT. Overall the rate of Toxoplasma infection in chicken was 10.04%. The prevalence of toxoplasmosis among free-ranging chickens was 27.1% but the rate in semi-industrial and industrial chickens was 12% and 2.02% respectively. The rate of seropositive chickens in titers of 1/16, 1/32, 1/64, 1/128, 1/256 and 1/512 was 5.88 %, 2.44 %, 1 %, 0.57 %, 0 %and 0.14 % respectively. Considering the high prevalence of toxoplasmosis in chickens, in the regions under study, control measures should be taken to prevent transmission of the infection to the animals and humans by Health and Veterinary organizations.